Mental health and psychological distress among Covid-19 frontline workers - Rahman, Mst Jakia; Alauddin, Md (Dhaka University Journal of Biological Sciences, 2023)
Covid-19 has caused significant distress around the globe. Apart from the evident physical symptoms in infected cases, it has caused serious damage to public mental health. The current research is an attempt to explore mental health and psychological distress of the Covid-19 frontline workers. One hundred and seventy-seven Covid frontline workers (88 male and 89 female) were asked to complete a questionnaire with questions about symptoms of depression, anxiety, stress, and mental health. The questionnaire included Depression, Anxiety and Stress Scales (DASS-21) and the Bangla version of the General Health Questionnaire (GHQ-12). The results revealed that mental health was negatively correlated with stress, anxiety, and depression. Both male and female frontline workers reported mild to moderate levels of depression, anxiety, and stress. Females reported significantly higher stress than males. However, frontline workers from different professions did not differ significantly on depression, anxiety, stress, and mental health. The findings point to develop strategy to support the mental health of frontline workers including designing psychological support and resilience-building interventions based on risk factors. Dhaka Univ. J. Biol. Sci. 32(2): 167-177, 2023 (July)